PERBEDAAN MODEL PEMBELAJARAN KOOPERATIF STAD DENGAN MODEL PEMBELAJARAN KONVENSIONAL TERHADAP PRESTASI BELAJAR MATEMATIKA - Asrining Asrining (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2015)
The low learning outcomes of students, it is due to the learning process that is dominated by traditional learning. At this learning atmosphere tends to teacher-centered classroom so that students become passive, therefore it is necessary to implement a learning strategy that can help students to understand the teaching material and its application in everyday life. Based on this, in this study it will be discussed whether there are differences in mathematics achievement subject matter sub gradient between students who are taught by STAD cooperative learning model and the conventional model of learning in class XI SMA Kartika IV-3 Surabaya. The purpose of this study was to determine differences in mathematics achievement between students who are taught by STAD cooperative learning model and conventional learning models. This study uses quantitative research. As the population is students in class XI MIA Kartika IV-3 Surabaya The sample consisted of students of class XI MIA 1, amounting to 25 students as the experimental class and the students of class XI MIA 2, amounting to 25 students as the control class. Data collection method used is to use the test method. Data in the form of student test results done once the post-test is to determine the value of learning mathematics achievement of students in each sample after treatments or treatments performed. From the analysis we found differences in mathematics achievement between students who are taught by STAD cooperative learning model and conventional learning models, in this case increased learning achievement in cooperative learning model STAD. With the calculation of the t-test is greater than the table or 4.98> 1.98 then H0 is rejected and H1 is accepted. The conclusion from this study is that there are differences in mathematics achievement subject matter sub gradient between students who are taught by STAD cooperative learning model and conventional learning models, characterized by differences in mathematics achievement. Keywords: thinking process , linguistic intelligence , mathematical logical intelligence, story problem.